Payment Data Processing in Web-Based Futsal Field Booking System (Futsal Sport Center Case Study) - Akhmad Sayuti; Rhaffi Ahmad Perdana; Irwansyah (Citra Air Nusantara, 2026)
The demand for futsal field rentals continues to increase along with the popularity of futsal among the public. However, the ordering and payment process is still done manually, causing various problems such as recording errors, long queues, and late payment confirmation. This study aims to design and build a web-based information system that can help the ordering process and manage payment data digitally. This system was developed using the Waterfall method with the PHP programming language and MySQL database, and tested using the black box testing approach. The main features provided include field reservations, schedule management, uploading proof of payment, and validation by the admin. The test results show that the system runs well and provides convenience for both tenants and managers. The implementation of this system provides technopreneurial added value in the form of operational efficiency, improved customer service, and the potential for expanding digital-based services.